Kemampuan Menulis Narasi - Adinda Putri Hanifa; Elsa Nurdiana Putri; Sakira Molania Jacky (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2024)
Writing is a complex ability to express thoughts and ideas into written form as a means of conveying messages. Narrative text is an essay that presents a series of events chronologically with the aim of entertaining, increasing knowledge, providing insight and aesthetic experience to the reader. The characteristics of a narrative text include containing a story with a narrative language style, having a clear storyline, containing events/conflicts, as well as elements such as theme, setting, plot, characters and point of view. The linguistic elements of narrative texts include the use of figurative words (metaphors), transitive and intransitive verbs, nouns, adjectives, phrases/clauses, and conjunctions to mark time order. The type of narrative text consists of informative, artistic and suggestive narratives. The structure of narrative text consists of orientation, complication, resolution, and reorientation. The steps for writing a narrative text include determining the theme, target audience, designing the story line, developing the story, arranging story elements, and understanding punctuation rules. The narrative writing assessment includes aspects of content/ideas, writing organization, language, and writing grammar.